2018
DOI: 10.1186/s12936-018-2250-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of temperature on insecticide toxicity against the malaria vectors Anopheles arabiensis and Anopheles funestus

Abstract: BackgroundIt is anticipated that malaria elimination efforts in Africa will be hampered by increasing resistance to the limited arsenal of insecticides approved for use in public health. However, insecticide susceptibility status of vector populations evaluated under standard insectary test conditions can give a false picture of the threat, as the thermal environment in which the insect and insecticide interact plays a significant role in insecticide toxicity.MethodsThe effect of temperature on the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 30 publications
1
85
0
Order By: Relevance
“…Wang et al [39] found that allethrin, belonging to nTCI, blocked the action potential of squid giant axons more strongly at 8 • C than at 23 • C, and therefore accounted for the negative TC of nerve blocking action of allethrin. Different kinds of pyrethroids, although all interact with the sodium channels, could show different temperature effects [40]. However, very little was found in the literature on the underlying mechanisms, especially the molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [39] found that allethrin, belonging to nTCI, blocked the action potential of squid giant axons more strongly at 8 • C than at 23 • C, and therefore accounted for the negative TC of nerve blocking action of allethrin. Different kinds of pyrethroids, although all interact with the sodium channels, could show different temperature effects [40]. However, very little was found in the literature on the underlying mechanisms, especially the molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…arabiensis . [ 37 ] A possible explanation was that the detoxification enzyme systems had been affected by the temperature elevation. Therefore, the following discussion on differential proteins will focus on the Sahelian region.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility test data are noisy ( 29 , 30 ) and the low data volumes typically seen in resistance monitoring ( Fig. 1 ) are particularly susceptible to issues of data noise.…”
Section: Discussionmentioning
confidence: 99%